Detection, transport, and retention of Toxoplasma gondii oocysts in saturated sandy porous media: Influence of electrolytes and natural organic matter in flow-through systems - Christian P. Pullano; Mahsa Ghorbani; Timothy J. Mutty; Sohib Gouasmia; Coralie L’Ollivier; Jitender P. Dubey; Aurélien Dumètre; Christophe J. G. Darnault (PLoS ONE, 2025)
Understanding the transport and retention of Toxoplasma gondii oocysts through soils and into ground and surface water is essential for determining the risk this parasite poses to water resources and human health worldwide. We studied here how various naturally occurring groundwater solutions containing different types of organic compounds (fulvic and humic acids) and electrolytes (NaCl, MgCl2, CaCl2) at different concentrations can affect the transport and retention of oocysts in engineered-saturated silica sand columns subjected to continuous flow to simulate the movement of groundwater through an aquifer. Breakthrough curve results from the qPCR analysis were then compared to non-reactive tracer tests to determine parameters that govern the transport of oocysts in saturated porous media. Though breakthrough of oocysts was observed in all tested solutions, higher ionic strength and ion valency resulted in greater oocyst retention. When both organic matter and electrolyte solutions were added to the systems, the electrolyte solutions displayed a far greater influence on parasite retention when compared to the influence of the organic matter alone. Collectively, this study demonstrates the pivotal role of soil groundwater solution chemistry in both the transport and retention of this important zoonotic parasite.